Demographic and clinical profile of patients with acute biliary pancreatitis: an experience in Patan academy of health sciences - Duwal, Santosh; Suwal, Bikesh; Maharjan, Santabir; Bhandari, Upendra (International Surgery Journal, 2024)
Background: Acute pancreatitis is one of the most common causes of acute abdomen encountered in emergency department with wide range of severity from mild self-limiting disease to severe and rapidly progressive illness leading to multi organ failure and even death. Gall stones are leading cause of acute pancreatitis. This study has been carried out to find out demographic pattern and clinical profile of patients with acute biliary pancreatitis. Methods: This is a prospective cross-sectional study carried out in the department of surgery in Patan academy of health sciences (PAHS) in the time period between May 1, 2021 and April 30, 2022. The process of data collection was started after obtaining ethical approval from institutional review committee (IRC) of PAHS, and written informed consent was obtained from patients. Total sampling was done and 66 patients were enrolled into the study, who were diagnosed as acute biliary pancreatitis. Data was analyzed with SPSS ver 25 and Microsoft excel 2016. Results: Out of total 66 patients in the study 25 (37.9%) were male and 41 (62.1%) were female with male: female ratio of 1:1.64. Mean age was 48.42±16.62 years. ranging from 16-88 years. Epigastric abdominal pain was predominant presenting symptoms accounting for 57 (86.4%) cases. Pleural effusion was most common complication seen in 17 (25.8%) cases. Mortality occurs in 2 (3%) cases, both of cases had severe pancreatitis. Only 21 (31.8%) patients underwent cholecystectomy among which 13 (19.7%) interval and 8 (12.1%) index cholecystectomy. Conclusions: Female gender with age group of 40-60 years. predominates acute biliary pancreatitis. Though most of the cases are mild and have benign course, severe cases and patients with advanced age are associated with high mortality. Acceptance of index cholecystectomy is very low.